Using Traditional Games to Improve Physical Fitness in Primary Schools - Rahmah, Yeni (Jurnal Pendidikan, Kesehatan dan Olahraga, 2023)
Physical education is an education that recognises human potential in the form of attitudes, actions and deeds that are given form, content and direction, and towards a perfect personality in accordance with human ideals. The game is an entertainment that is much sought after and played by many people, both children and adults. Even in the existing school environment with cheap and affordable materials for children. Physical activity is an indicator of a dynamic level of health. This article is an academic work written and contains ideas, opinions or facts to be published in a research journal, the writing process follows certain composition rules to obtain academic articles based on the results of a field. The characteristics of primary school children are a period in which the possibility of achieving excellent growth and development in the future exists. The purpose of all education is to develop physical fitness and motor skills, critical thinking, social skills, reasoning, emotional stability, moral action, the appearance of the application of a healthy lifestyle and a clean environment through selected and systematically planned physical education activities to achieve educational goals. The importance of good physical growth and movement development in the growing years of primary school children remains. The importance of fitness for people because the factor is very supportive of the results of operations that need to be supported. To maintain fitness, you need to arrange a regular activity pattern so that you can exercise maximally for daily activities. This affects the physical condition and body condition is an important thing in life to support all daily activities. This affects the physical condition and body condition of students is an important thing in life to support all daily activities. In addition to teachers who need creativity and innovation, it also takes the role of students who must play an active role in learning physical education.